The Impact of Macroeconomic Variables on Equity Risk Premium: Evidence from Sectoral Analysis in Vietnam Using Bounds Testing Approach - Nguyen, Thi Thuy Vinh; Nguyen, Minh Thuy; Pham, Xuan Truong; Le, Kieu Phuong (Journal of International Economics and Management, 2016)
This study investigates the impact of change of macroeconomic variables on equity risk premium of Ho Chi Minh stock market and some important sectors for period January 2007- September 2015. The paper applies bounds testing approach to cointegration to find the long run and short run relationships. The results show that there are long run relationships between equity risk premium for both market and sectoral analysis with some selected macroeconomic variables. In the long run, inflation rate exert negative impact on excess returns except for the financial sector. However, in the short run, an increase in exchange rate volatility significantly reduces equity risk premium of market and all sectors. These findings shed some light for monetary authorities to implement monetary policy.